Changes in blood pressure associated with lead, manganese, and selenium in a Bangladeshi cohort. (May 2019) - Bulka, Catherine M.; Scannell Bryan, Molly; Persky, Victoria W.; Daviglus, Martha L.; Durazo-Arvizu, Ramon A.; Parvez, Faruque; Slavkovich, Vesna; Graziano, Joseph H.; Islam, Tariqul; Baron, John A.; Ahsan, Habibul; Argos, Maria
Abstract: Background: Heavy metal contamination is widespread in Bangladesh. Previous studies have observed lead increases blood pressure over time. However, the role of other metal contaminants and essential micronutrients, which could also adversely affect blood pressure or act as protective factors, is understudied. Objectives: We therefore evaluated the associations of lead, manganese, and selenium with blood and pulse pressure trajectories. Methods: We prospectively followed placebo-assigned participants nested within a randomized trial for the prevention of arsenic-related skin cancer (n = 255). Blood lead, manganese, and selenium were measured at baseline; blood pressure was measured at baseline and at 3 biennial follow-up examinations. Mixed-effect linear regression models were used to estimate associations with average annual changes in systolic, diastolic, and pulse pressure. Results: In models simultaneously adjusted for baseline blood lead, manganese, and selenium concentrations in addition to other potential confounders, lead was linearly associated with increases in systolic blood pressure, but not with diastolic blood pressure or pulse pressure. A non-linear association was observed for manganese, such that mid-range concentrations were associated with decreases in systolic, diastolic, and pulse pressure. Baseline selenium concentrations in the highest quartile were also associated with longitudinal decreases in both systolic and diastolic blood pressure, while null associations were observed with pulse pressure. In exploratory analyses, the combination of mid-range manganese and high selenium concentrations completely offset lead-associated increases in blood and pulse pressure. Conclusions: The results indicate a direct, linear association of lead exposure with systolic blood pressure, and manganese and selenium exposures within certain ranges may have a blood pressure-lowering effect in this population. Highlights: Metal contamination is endemic in Bangladesh where elevated exposure to certain toxic metals can result in hypertension. Epidemiologic research on other metals, including essential nutrients, in relation to blood pressure has been sparse. ILead was related to higher blood pressure, whereas manganese and selenium within certain ranges were associated with declines. This study highlights the potential for manganese and selenium as anti-hypertensive agents in a lead-exposed population. Abstract : The findings of this study suggest toxic lead exposures remain a significant public health problem in Bangladesh where high levels are associated with high blood pressure; however, the nutritionally essential micronutrients manganese and selenium appear to confer protection from the hypertensive effects of lead.